Congestion avoidance in 6G networks with V Gradient Geocast Routing Protocol - Sahoo, Arundhati; Tripathy, Asis Kumar (Scientific reports, 2025)
This is a moment of heavy necessity for a dependable internet connection in the modern world, which is used to engage in business dealings, communicate with other people, entertain oneself, and lead a daily life. Therefore, a Wi-Fi 6 router must have an internal wire-free connection within a house or business. However, as they depend on the weather and are installed in ways that expose them to infiltration, they are vulnerable. The increased demand for Internet services for business, communication, and leisure activities due to poor weather puts added stress on the network, slowing down the speeds and increasing congestion. The bottom line is to prioritize traffic and lower latency and convergence time to improve network performance under less-than-ideal weather conditions. This will be realized using highly technical approaches such as the mini-batch gradient descent optimization algorithm for network optimization and the V Gradient Geocast Routing Protocol for effective routing. The proposed enhanced congestion avoidance model with V Gradient Geocast Routing Protocol in 6G networks under unfavorable weather conditions attains an accuracy of 98.85%.